Symbolic behaviour at places of social activity beyond the domestic area in the Ionian neolithic - Stratouli, Georgia (Documenta Praehistorica, 2005)
This paper suggests a reassessment of the role of caves during the Neolithic in Greece. Some of these cavities could have hosted performative and ritual events, or other kinds of social and/ or symbolic activities and, therefore, could be treated as forms of monuments. These issues are discussed on the basis of Drakaina Cave, located in the Poros Gorge on Kephalonia Island in the Ionian Sea. The archaeological evidence of the cave (e.g. the construction of lime plastered floors, the deliberate deposition of associated artefacts) is traced on three main scales: symbolism, monumentality, and the significance of the cave's landscape for Neolithic society. Moving away from the site, it is argued that the gorge of Poros itself was a powerful topographic feature, constituting a symbolic resource in the landscape and, thus, a valued site which contributed to the formation of the biography, identity and politics of the Neolithic community in the region.
Keywords: Grčija; Greece; Kefalonija; arheološke najdbe; neolitik; jame; Jame, Slunj; artefakti; običaji